Aplikasi Presensi Pegawai dengan Metode Face Recognize dan Location-Based Service berbasis Android - Efendi, Achmad Oky; Wardoyo, Ari Eko; Handayani, Luluk (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
Presence is a one of main thing for a State Civil Apparatus (ASN). However, in its implementation, the ASN attendance process currently still uses conventional methods and finger machines, which causes several problems, such as ineffectiveness, inefficiency, and vulnerability to fraud. This research is aimed to develop a presence application using Android-based face recognition and location-based service methods. This study type is research and development use the Software Development Life Cycle (SDLC) Spiral that focuses on paying attention to project risks. The liason or data collection stage used is a literature study by looking for relevant study, then direct observation in the field interviews with BKPSDM Bondowoso regarding presence issues, and a questionnaire to collect feedback from respondents as material for further application development, then the data collection results will be used to analyze needs, features and application specifications. The risk analysis stage aims to identify risks that may occur. The engineering stage of the application was built using the Flutter framework and RestfulAPI. The results of application testing state that the application can perform according to its functionality and needs. The study results is an Android application that aims to assist ASN in facilitating attendance via smartphones. According to a survey of 500 people, the application was positively received by Bondowoso County Government.